Representasi dan Resistensi Perempuan dalam Sihir Perempuan Karya Intan Paramaditha: Perspektif Kritik Sastra Feminis - Ihwandi Ihwandi; Sovia Wulandari; Dwi Rahariyoso; Irma Suryani (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze and comprehensively describe the representation of women in Sihir Perempuan, a collection of short stories by Intan Paramaditha, using the framework of feminist literary criticism. The research employed a qualitative descriptive method with content analysis as the primary analytical technique. The main data consisted of narrative texts, dialogues, and characters’ inner monologues found in ten selected short stories from the anthology. Data were collected through close reading and note-taking techniques, while theoretical triangulation was applied to ensure data validity. The findings reveal that the representation of women in the anthology is structurally categorized into three major dimensions. First, the physical dimension highlights bodily exploitation, clothing as a marker of social status, and the deconstruction of patriarchal beauty standards. Second, the psychological dimension portrays inner anxiety, existential trauma, obsession, and neurotic fear resulting from both domestic and public pressures. Third, the social dimension demonstrates the complexity of women's roles as subordinates within family institutions, secretaries subjected to workplace harassment, and victims of social marginalization due to mystical stigmas and collective rumors. Through the use of Gothic horror aesthetics and the deconstruction of conventional fairy tales, Intan Paramaditha not only depicts women's oppression but also articulates female agency, resistance, and radical forms of rebellion aimed at challenging and dismantling patriarchal social structures.